The effect of sr-cofe2o4 nanoparticles with different particles sized as additives in cip-based magnetorheological fluid - Nugroho, K. C. (MDPI AG, 2021)
This study investigated the effect of adding strontium (Sr)-doped cobalt ferrite (CoFe2O4) nanoparticles in carbonyl iron particle (CIP)-based magnetorheological fluids (MRFs). Sr-CoFe2O4 nanoparticles were fabricated at different particle sizes using co-precipitation at calcination temperatures of 300 and 400◦C. Field emission scanning electron microscopy (FESEM) was used to evaluate the morphology of the Sr-CoFe2O4 nanoparticles, which were found to be spherical. The average grain sizes were 71–91 nm and 118–157 nm for nanoparticles that had been calcinated at 300 and 400◦C, respectively. As such, higher calcination temperatures were found to produce larger-sized Sr-CoFe2O4 nanoparticles. To investigate the rheological effects that Sr-CoFe2O4 nanoparticles have on CIP-based MRF, three MRF samples were prepared: (1) CIP-based MRF without nanoparticle additives (CIP-based MRF), (2) CIP-based MRF with Sr-CoFe2O4 nanoparticles calcinated at 300◦C (MRF CIP+Sr-CoFe2O4-T300), and (3) CIP-based MRF with Sr-CoFe2O4 nanoparticles calcinated at 400◦C (MRF CIP+Sr-CoFe2O4-T400). The rheological properties of these MRF samples were then observed at room temperature using a rheometer with a parallel plate at a gap of 1 mm. Dispersion stability tests were also performed to determine the sedimentation ratio of the three CIP-based MRF samples.